2014
DOI: 10.1158/0008-5472.can-13-0544
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Mouse Model of Invasive Endometrial Cancer Driven by Concurrent Loss of Pten and Lkb1 Is Highly Responsive to mTOR Inhibition

Abstract: Signals from the tumor suppressors PTEN and LKB1 converge on mTOR to negatively regulate its function in cancer cells. Notably, both of these suppressors are attenuated in a significant fraction of human endometrial tumors. In this study, we generated a genetic mouse model of endometrial cancer driven by concomitant loss of these suppressors to gain pathophysiological insight into this disease. Dual loss of Pten and Lkb1 in the endometrial epithelium led to rapid development of advanced endometrioid endometria… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…Mice with homozygous endometrial LKB1 inactivation underwent diffuse malignant transformation of the entire endometrium with rapid extra uterine spread and death suggesting that LKB1 inactivation was sufficient to promote the development of invasive EC (Contreras et al 2010). In a mouse model of EC, dual loss of PTEN and LKB1 in the endometrial epithelium led to rapid development of advanced EEC with 100% penetrance and short host survival (Cheng et al 2014). Co et al (2014) analyzed LKB1 gene expression in low and high grade EECs and found that LKB1 is a direct transcriptional target of p53.…”
Section: Cell Signaling Pathwaysmentioning
confidence: 99%
“…Mice with homozygous endometrial LKB1 inactivation underwent diffuse malignant transformation of the entire endometrium with rapid extra uterine spread and death suggesting that LKB1 inactivation was sufficient to promote the development of invasive EC (Contreras et al 2010). In a mouse model of EC, dual loss of PTEN and LKB1 in the endometrial epithelium led to rapid development of advanced EEC with 100% penetrance and short host survival (Cheng et al 2014). Co et al (2014) analyzed LKB1 gene expression in low and high grade EECs and found that LKB1 is a direct transcriptional target of p53.…”
Section: Cell Signaling Pathwaysmentioning
confidence: 99%
“…13 Almost all AA SMGs identified in this study were found in patients with endometrioid UCEC, including 20 patients that were double-mutant for MTOR and PTEN. MTOR is thought to be overactive in endometrial cancers with inactive PTEN, 43 and as MTOR is a major posttranslational inhibitor of autophagy, it is tempting to speculate that autophagy may be less active in type I endometrioid tumors. It is noteworthy that we observed a recurrent truncating mutation (R1321*) in autophagy induction complex member RB1CC1 in 3 UCEC patients, along with a predicted damaging substitution (S93L) in 2 additional patients, suggesting autophagy induction may be compromised in these endometrioid UCEC patients.…”
mentioning
confidence: 99%
“…Whereas the individual knockout of each gene causes only a low incidence of cancer, double knockouts markedly increase cancer incidence (1,2). However, the molecular mechanism by which their combined loss leads to cancer is not fully understood.…”
mentioning
confidence: 99%